Discovery-driven growth : a breakthrough process to reduce risk and seize opportunity - McGrath, Rita Gunther; MacMillan, Ian C., 1940- (Boston, Mass. : Harvard Business Press, 2009)
You've been charged with growing your business. Incremental growth can no longer deliver the results you need. You need truly dynamic growth and you need to achieve it without risking a hugely expensive gamble. This book shows readers how to encourage innovative ventures with minimum risk.
Driving corporate growth with the right disciplines -- Creating your growth framework -- Aligning the organization for growth -- Designing specific growth initiatives -- Designing the business model architecture -- Creating reverse financials and the assumption checklist -- Actively managing and redirecting projects -- Practicing the necessary art of disengagement -- Implementing discovery-driven growth -- Sustaining discovery-driven growth.
Includes bibliographical references (pages 227-235) and index.
Description based on print version record.
Keywords: Corporations -- Growth -- Management; Organizational effectiveness; Strategic planning; Efficacité de l'organisation.; Planification stratégique; Corporations -- Growth -- Management; Organizational effectiveness; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books